The metaphysical theory of the state : a criticism - Hobhouse, L. T. (Leonard Trelawny), 1864-1929 (Routledge revivals., 2009)
Originally published in 1918, this enduring work by renowned sociologist and Liberal politician Leonard Trelawny Hobhouse encompasses a series of five key lectures, first delivered at the London School of Economics in the autumn of 1917. Outlining Hobhouse's theories on social investigation, freedom, law and the will of the state, this edition revives an important work, which has long been unavailable.